A Novel Metallothionein Gene from Mussel, Hyriopsis cumingii: Identification and Expression under Lanthanum Exposure. Issue 4 (August 2014) - Yang, Shoubao; Wei, Min; Yang, Xiaoxue; Wang, Heng; He, Liping; Li, Chen
Abstract Metallothionein (MT) is a superfamily of cysteine‐rich, metal‐binding, low‐molecular‐weight proteins that participate in the storage, transportation, and metabolism of the trace metal elements. In this study, a novel MT gene from Hyriopsis cumingii was cloned (designated HcMT1); it shared 59.2% identity with previously published MT sequence of H. cumingii and 56.1–97.3% identity with other MT genes from mollusks. The expression level of HcMT1 in various tissues was determined by real‐time polymerase chain reaction. Relatively higher expression levels were observed in digestive gonad, mantle, and gill, and the expression level in hemocytes was significantly upregulated by lanthanum (La3+) exposure. The nucleotide sequence of HcMT1 amplified from genomic DNA is identical to the cDNA template group under La3+ exposure, which indicated that HcMT1 is an intronless gene. These results indicate that HcMT1 may play an important role in La3+ metabolism.